Analisis Faktor yang mempengaruhi Persepsi Harga, Promosi, dan Kualitas Pelayanan terhadap Loyalitas Konsumen melalui Kepuasan Konsumen sebagai Variabel Intervening (Studi Kasus pada Warung Bebek Jaya Antika) - Rohani Rohani (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This thesis uses quantitative research which aims to determine whether the perception of price, promotion and service quality has a direct or indirect influence on consumer loyalty and customer satisfaction. And also whether consumer satisfaction also has a direct effect on consumer loyalty. This research uses descriptive quantitative. The number of samples taken as many as 100 respondents. Respondents used in this study were consumers of the Warung Duck Jaya Antika. The technique applied in this research is probability sampling or random sampling, taking random samples. Data collection techniques by giving questionnaires to respondents, interviews and documentation. In proving and analyzing this, validity and reliability tests are used, multiple linear regression, f and t tests, path analysis tests and determination tests are used.The hypothesis which states that price, promotion, and service quality has a direct effect on customer satisfaction is proven. The hypothesis which states that price, promotion, and service quality has a direct effect on consumer loyalty is proven. The hypothesis which states that consumer satisfaction has a direct effect on consumer loyalty is proven. price, promotion, and service quality have an indirect effect on consumer loyalty through customer satisfaction as a proven intervening variable.Keywords: Price Perception, Promotion, Service Quality, Consumer Loyalty and Consumer Satisfaction